The effect of postoperative vaginal progesterone in ultrasound-indicated cerclage to prevent preterm birth. (3rd August 2021) - Park, Jee Yoon; Jung, Young Mi; Kook, Song-Yi; Jeon, Se Jeong; Oh, Kyung Joon; Hong, Joon-Seok
Abstract: Objectives: To compare pregnancy outcomes according to the use of postoperative vaginal progesterone in patients who underwent ultrasound-indicated cerclage. Methods: This was a retrospective cohort study of 86 consecutive asymptomatic singleton pregnancies who had undergone cerclage because of incidentally found short cervical length under 20 mm through transvaginal ultrasound between 16° /7 and 24 6/7 weeks' gestational age. Outcomes were compared according to the use of vaginal progesterone after cerclage. Primary outcome measure was preterm delivery < 34 weeks of gestation. Results: (1) The frequency of preterm delivery < 34 weeks of gestation was significantly lower in patients with postoperative vaginal progesterone than those without (2.2 versus 18.4%, p  = .021); (2) the median gestational age at delivery in the postoperative vaginal progesterone group was significantly longer than the control group (38.3 weeks (interquartile range, 37.5–39.1 weeks) versus 37.3 weeks (interquartile range 33.9–38.6 weeks), p  = .020); (3) Multivariable logistic regression analysis demonstrated the use of vaginal progesterone after cerclage was found to be independently associated with decrease in preterm delivery before 34 weeks (Odds ratio 0.10; 95% confidence interval, 0.01–0.93) and 37 weeks (Odds ratio 0.24; 95% confidence interval, 0.07–0.85). Conclusions: The use of vaginal progesterone was associated with lower rates of preterm birth before 34 and 37 weeks of gestation in women who underwent ultrasound-indicated cerclage placement.